2012
DOI: 10.1007/s00894-012-1693-8
|View full text |Cite
|
Sign up to set email alerts
|

The average local ionization energy as a tool for identifying reactive sites on defect-containing model graphene systems

Abstract: In a continuing effort to further explore the use of the average local ionization energy [Formula: see text] as a computational tool, we have investigated how well [Formula: see text] computed on molecular surfaces serves as a predictive tool for identifying the sites of the more reactive electrons in several nonplanar defect-containing model graphene systems, each containing one or more pentagons. They include corannulene (C20H10), two inverse Stone-Thrower-Wales defect-containing structures C26H12 and C42H16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…χ̅ also appears in the theoretical framework of moments of the electron distribution, pursued by Pettifor, Burdett, and Lee, for describing factors behind solid-state structure. Politzer, Murray, and co-workers have investigated the average local ionization energy, essentially a spatially distributed equivalence of χ̅, on isosurfaces of constant electron density, within the contexts of molecular reactivity, electronegativity, polarizability, , and other properties …”
Section: Where It Begins: the Average Electron Binding Energy χ̅mentioning
confidence: 99%
“…χ̅ also appears in the theoretical framework of moments of the electron distribution, pursued by Pettifor, Burdett, and Lee, for describing factors behind solid-state structure. Politzer, Murray, and co-workers have investigated the average local ionization energy, essentially a spatially distributed equivalence of χ̅, on isosurfaces of constant electron density, within the contexts of molecular reactivity, electronegativity, polarizability, , and other properties …”
Section: Where It Begins: the Average Electron Binding Energy χ̅mentioning
confidence: 99%
“…(10) we havē (r) = 1 ρ(r) r|F |r r |γ |r dr . (11) In the HF method,F is the Fock operator whose coordinate representation is 25…”
Section: Average Local Electron Energy For One-determinantal Scf mentioning
confidence: 99%
“…The electrostatic potentials were mapped from the Gaussian wave functions on the surface defined by the 0.004 e – Å −3 contour of electron density. This surface was chosen as it has been shown that the differences on electrostatic potential surfaces of complexes with different metals can be noticed at this value …”
Section: Methodsmentioning
confidence: 99%